2014
DOI: 10.1007/s00299-014-1563-1
|View full text |Cite
|
Sign up to set email alerts
|

Improving the efficiency of isolated microspore culture in six-row spring barley: II-exploring novel growth regulators to maximize embryogenesis and reduce albinism

Abstract: Two alternative cytokinins, thidiazuron and meta-topoline, were tested in isolated microspore culture on recalcitrant barley genotypes (six-row, spring), and green plant regeneration was improved substantially. Doubled-haploid (DH) plants are coveted in plant breeding and in genetic studies, since they are rapidly obtained and perfectly homozygous. In barley, DHs are produced mainly via androgenesis, and isolated microspore culture (IMC) constitutes the method offering the greatest potential efficiency. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The applicability of the isolated microspore system is dependent on the proportion of obtained embryos converted into green plants. For this reason much effort is dedicated to establishing efficient protocols of the microspore culture (Esteves et al 2014). It is well documented that in barley anther culture additional Cu 2+ supplementation during both the pretreatment and the induction phase of androgenesis improves GP regeneration (Jacquard et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The applicability of the isolated microspore system is dependent on the proportion of obtained embryos converted into green plants. For this reason much effort is dedicated to establishing efficient protocols of the microspore culture (Esteves et al 2014). It is well documented that in barley anther culture additional Cu 2+ supplementation during both the pretreatment and the induction phase of androgenesis improves GP regeneration (Jacquard et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this alternative cytokinin has not been used to induce microspore embryogenesis by anther or isolated microspore cultures. Esteves et al (2014) recently tested meta-Topolin in the regeneration medium of isolated microspore culture of recalcitrant barley genotypes. It increased embryo differentiation into green plants by 2.9-fold.…”
Section: Introductionmentioning
confidence: 99%
“…TDZ improved green plant regeneration in recalcitrant six-row, spring barley genotypes (Esteves, Clermont, Marchand, & Belzile, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…A previous study suggested that adding TDZ to the inducing medium is more efficient and can even replace the cytokinin benzylaminopurine (BAP) in isolated microspore culture; TDZ also affected peanut somatic embryogenesis presumably (Murch, Victor, Krishnaraj, & Saxena, ). TDZ improved green plant regeneration in recalcitrant six‐row, spring barley genotypes (Esteves, Clermont, Marchand, & Belzile, ). TDZ could be used to enhance the gynogenesis of unfertilized ovule cultures of Chinese long cucumber (Li, Si, Cheng, Li, & Liu, ); high induction frequencies (7.85%–12.14%) were found at the time of anthesis with concentrations of 0.03–0.07 mg/dm 3 .…”
Section: Discussionmentioning
confidence: 99%